Towards an Islamic common market: are oic countries heading the right direction? - Mohd Amin, Ruzita; Hamid, Zarinah (IIUM, 2009)

(untitled)
Economic cooperation through trade has been one of the important agendas of the Organisation of the Islamic Conferences (OIC) since its establishment in September 1969. This study analyzes intra-trade potentials by using the Revealed Comparative Advantage (RCA) Indices on five countries that are signatories to the Framework Agreement on Trade Preferential System among the Member States of the OIC. These countries are Jordan, Malaysia, Pakistan, Turkey and the United Arab Emirates (UAE). Sectors that show potential for intra-trade among OIC countries are identified based on the RCA indices. The corresponding MFN weighted average applied rates are also examined to determine the specific sectors that would benefit from tariff reductions under the PRETAS. The findings of the analysis serve to provide an indication as to whether the implementation of the TPS-OIC is strategically headed towards the right direction. Such information will be useful for member countries to formulate strategies that would foster closer trade relations among themselves in their effort towards establishing an Islamic Common Market.